Extradural Hydatid Cyst of the Lumbo-Sacral Spine - Dahal, Riju; Gurung, Pritam; Dahal, Sujat; Shrestha, Resha; Acharya, Samir; Rajbhandhari, Pravesh; Shrestha, Pranaya; Pant, Basant (Nepal Journal of Neuroscience, 2019)
Primary spinal hydatid cyst is a rare and uncommon entity but a significant manifestation of hydatid disease. Here, we report a case of primary extramural hydatid cyst of the sacral region causing cord compression. Pre-operative differential diagnosis was that of Tarlov cyst owing to the radiological appearance and location of the cyst. The diagnosis of hydatid cyst was established intra-operatively which was later confirmed by histopathology report. Hydatidcyst may not fall under differential diagnosis of extramural lesions of the spine due to its rarity but should be kept under high suspicion in endemic countries.